Participation of silicon ions in the tolerance and plasticity of plants Phragmites australis to a soil moisture reduction - Nedukha, O.M.; Kordyum, E.L. (Reports of the National Academy of Sciences of Ukraine, 2019)
The results of studies of the localization and the silicon content in the leaves of air-water and terrestrial plants Phragmites australis, which grew on the banks of the Dnipro River (in the zone of Kiev) are presented. For the study of the Si content in leaves, cytochemical and structural methods are used. Classical biochemical methods are used to analyze the water content of the samples and the moisture content of the soil, on which the reed plants grew. For the analysis, we took leaves in the vegetative growth phase. The presence and subcellular localization of silicon ions are studied with the use of a laser confocal microscope (LSM 5, Zeiss, Germany) and a scanning electron microscope (with X-ray unit EX-S4175GMU, JEOL, Japan). The presence of silicon amorphous and crystalline inclusions in the periclinal cell walls of main epidermal cells, trichomes, stomatal cells, and over the leaf veins of air-water and terrestrial reed plants is shown by confocal microscopy. For the first time, a significant increase in the content of amorphous and crystalline silicon in the epidermis of leaves of this species of terrestrial plants by microscopy and X-ray analysis is revealed. It has been established that the cells of abaxial epidermis, in particular, cells around stomata and trichomes, trichomes and cells above veins, are the main accumulators of silicon in the leaves. It is assumed that such localization and increased content of silicon optimize the water balance of terrestrial plants and thus increase their resistance to soil drought. It is proposed to strengthen attention to the role of silicon in the adaptation of plants to adverse changes in abiotic environmental factors.